2022
DOI: 10.20944/preprints202208.0454.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spectroscopy Study of Isothermal Spin State Switching in a Fe (II) Spin Crossover Molecular Thin Film

Abstract: Using optical characterization, it is evident that the spin state of the spin crossover molecular complex [Fe{H2B(pz)2}2(bipy)] (pz = tris (pyrazol-1-1y)-borohydride, bipy = 2,2’-bipyridine) depends on the ferroelectric polarization of an adjacent thin film of the polymer ferroelectric polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP). The UV-Vis spectroscopy reveals that room temperature switching of [Fe{H2B(pz)2}2(bipy)] molecules in bilayers of PVDF-HFP/[Fe{H2B(pz)2}2(bipy)] as a function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…While several methods have been suggested to control switching between spin states [112,124], it has been found that by changing the ferroelectric polarization, the spin state occupancy of a very thin spin crossover molecular film can be manipulated [9,[125][126][127]. Thus, one possibility is using a ferroelectric material in the interface [127,128].…”
Section: Ferroelectric Substrate Manipulation Of the Spin Statementioning
confidence: 99%
See 1 more Smart Citation
“…While several methods have been suggested to control switching between spin states [112,124], it has been found that by changing the ferroelectric polarization, the spin state occupancy of a very thin spin crossover molecular film can be manipulated [9,[125][126][127]. Thus, one possibility is using a ferroelectric material in the interface [127,128].…”
Section: Ferroelectric Substrate Manipulation Of the Spin Statementioning
confidence: 99%
“…The thickness of the PVDF-HFP layer in PVDF-HFP/[Fe(H 2 B(pz) 2 ) 2 (bipy)] bilayer films plays a crucial role in achieving an optimal functionality of switching to different spin states by altering the polarity [125]. Moreover, the spin state of the [Fe(H 2 B(pz) 2 ) 2 (bipy)] thin film tends to be locked in a specific spin state depending on the direction of the polarization at the interface with organic ferroelectric PVDF-TrFE (polyvinylidene fluoride with trifluoroethylene) [126].…”
Section: Ferroelectric Substrate Manipulation Of the Spin Statementioning
confidence: 99%
“…32,37,38 Notably, intermolecular interactions have been widely studied and the hydrogen bonding network, pi-pi stacking 39 and even H-H van der Waals contacts have been proven to play a crucial role in cooperativity and hysteresis loop width. 40,41 Beyond the crystal structure, the shaping of SCO complexes was investigated for several years to form nanomaterials, 19,42 thin or thick films, 43,44 submonolayers, 45,46 composites with polymers. 47 Most of these material forms lead to modification of the SCO features, which shed light on the multiscale nature of the SCO properties and triggered new approaches to this phenomenon.…”
Section: Introductionmentioning
confidence: 99%